Weight lifting and type II aortic dissection: A case report - Ragucci, M. V.; Thistle, H. G. (The Journal of Sports Medicine and Physical Fitness, 2004)
The case of a 28-year-old previously healthy male with a 13-year history of weight lifting is described. The patient presented to the emergency department complaining of severe anterior chest pain beginning during a workout. Following transthoracic echocardiogram and computerized tomogram the diagnosis of an ascending aortic dissection was made. The patient was taken emergently for surgical repair of an incompetent aortic valve and type II aortic dissection. Histopathologic examination of the aorta showed cystic medial degeneration. This is the first reported case of a type II aortic dissection secondary to cystic medial degeneration and the hemodynamic stresses of weight lifting. Physicians should be aware of this potentially catastrophic entity in weight lifters.